Activating Room‐Temperature Phosphorescence of Organic Luminophores via External Heavy‐Atom Effect and Rigidity of Ionic Polymer Matrix. Issue 36 (6th August 2021) - Yan, Zi‐Ang; Lin, Xiaohan; Sun, Siyu; Ma, Xiang; Tian, He
Abstract: Pure organic room‐temperature phosphorescence (RTP) materials have attracted wide attention for their easy preparation, low toxicity, and applications in various fields like bioimaging and anti‐counterfeiting. Developing phosphorescent systems with more universality and less difficulty in synthesis has long been the pursuit of materials scientists. By employing a polymeric quaternary ammonium salt with an ionic bonding matrix and heavy atoms, commercial fluorescent dyes are directly endowed with phosphorescence emission. In a single amorphous polymer, the external heavy‐atom effect generates excited triplet states and the rigid polymer matrix stabilizes them. This study put forward a new general strategy to design and develop pure organic RTP materials starting from existing library of organic dyes without complicated chemical synthesis. Abstract : A doping strategy to directly transform commercial fluorescent dyes to pure organic, amorphous phosphorescent materials is developed via a single ionic polymer. The external heavy‐atom effect generates the triplet states, while the rigid ionic bonding matrix inhibits the nonradiative decay. This general strategy provides a method to activate room‐temperature phosphorescence (RTP) and a powerful tool for studying triplet states.